Avaliação da polarização dos macrófagos em pacientes infectados por Helicobacter pylori e a relação com a susceptibilidade do hospedeiro - TEIXEIRA, Selma Maluf (2021)
Helicobacter pylori is one of the most prevalent pathogens of the human species. Helicobacter pylori-induced chronic gastritis is an important risk factor for the development of gastric and duodenal ulcers and gastric adenocarcinoma. The immune response of the gastric mucosa caused by the bacteria is characterized by the presence of macrophages. These cells are considered important regulators of the immune response. According to the activation pathway, macrophages can shift their response to two opposite poles, known as M1 and M2, which can lead to varied clinical outcomes in many diseases. However, the functional profile of macrophages in Helicobacter pylori infection is not well defined. Thus, the objective of this study was to investigate whether the presence of H. pylori per si could induce the polarization of macrophages and whether this polarization would be associated with a greater bacterial load and a greater severity of the gastric mucosal inflammatory response. First, we performed a brief bibliographic review addressing the theme of assessing the polarization of macrophages in Helicobacter pylori infection, in which we observed few studies on human infection. One of them demonstrated M1 profile in infected patients with atrophic gastritis, indicating that excessive response or prolonged maintenance of the M1 polarization profile can lead to tissue damage and contribute to the pathogenesis of the infection. In addition, we address the pathogen's escape mechanisms to host immune responses. Then, we investigated macrophages polarization in H. pylori infected patients by immunohistochemistry of gastric mucosa. A cross-sectional study was conducted with 73 dyspeptic patients undergoing upper gastrointestinal endoscopy and diagnostic tests for H. pylori (urease and histopathological test) on biopsies of the gastric mucosa. The endoscopic diagnosis evaluated the presence of mild pangastritis or erosive pangastritis / peptic ulcer. The gastric mucosa was histologically evaluated to determine the presence of atrophy, metaplasia (pre-neoplastic lesions) and density of H. pylori. Of all the patients examined, 36 were H. pylori negative and 37 H. pylori positive. The patients were separated into three groups: a negative H. pylori group (n = 36), a group infected with H. pylori without pre-neoplastic lesions (n = 16) and another group infected with pre-neoplastic lesions (n = 21). Through the immunohistochemistry technique in the gastric mucosa, the expression of F4/80 (macrophage marker) and markers for the polarization profiles M1 (iNOS, TNF, HLA-DR) and M2 (Arginase, IL-10, CD163). In addition, Arginase activity was measured in patients' plasma. After analyzing the results, analyzes of the association between variables were performed. We observed that patients that H. pylori infected had a higher concentration of macrophages marked with Arginase and CD163, but did not show changes in the polarization markers iNOS, TNF-α, HLA-DR or IL-10, suggesting an M2 polarization profile. Macrophages marked with Arginase and CD163 were in greater numbers in patients with high bacterial load and chronic gastritis without pre-neoplastic lesions, compared to controls. IL-10 expression was lower in patients with higher bacterial density. Arginase expression was greater in the gastric mucosa of patients infected with erosive gastritis / peptic ulcer than controls with the same diagnosis. There was no correlation between Arginase expression in the mucosa and activity in the plasma. We conclude that one of the strategies of H. pylori to escape the pro-inflammatory response (M1) of the mucosa is to induce M2 macrophages. Thus, a low-grade inflammatory environment in the gastric mucosa, in response to infection, may be favorable for the persistence of the bacteria. However, bacterial load can be an imbalance factor in this tolerogenic profile. Furthermore, the lack of correlation between the expression of systemic and mucosal Arginase suggests that the bacterium promotes the modulation of the immune and inflammatory response at the site of infection. A greater understanding of the role of macrophage polarization in chronic gastritis associated with H. pylori infection can help to understand the immunopathology of infection with H. pylori and support future therapeutic and diagnostic approaches.